Minimal vertex separators and new characterizations for dually chordal graphs - De Caria, Pablo Jesús (2009)
Many works related to dually chordal graphs, their cliques and neighborhoods were published. We will undertake a similar study but by considering minimal separators and their properties. Moreover we find new characterizations of dually chordal graphs.